The Effect of Pop-Up Book Learning Media on Civics Learning Outcomes of Fourth Grade Students in Indonesian Elementary Schools - Minar Trisnawaty Lumbantobing; Abather Rahi Saadoon (STAI Hubbulwathan Duri, 2026)
This study examines the effect of pop-up book learning media on students’ learning outcomes in Civics (Pancasila Education) at the elementary school level. The use of conventional teaching methods often makes Civics learning less engaging, which can result in low student learning outcomes. Therefore, innovative and interactive learning media are needed to enhance students’ understanding and participation during the learning process. This research employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest model. The participants were 23 fourth-grade students of SD Negeri 091608 Sinaksak selected through saturated sampling. Data were collected using a multiple-choice test consisting of 25 items administered before and after the implementation of pop-up book learning media. The data were analyzed using descriptive statistics, a normality test (Shapiro–Wilk), N-gain analysis, and a paired sample t-test with the assistance of SPSS. The results showed a significant improvement in students’ learning outcomes. The average pretest score was 51.09, while the posttest average increased to 86.74. The normality test indicated that both datasets were normally distributed (p 0.05). The N-gain score was 0.74, categorized as high, with an effectiveness level of 74.14%. Furthermore, the paired sample t-test showed a significant difference between pretest and posttest scores (t = 26.51, p 0.05). These findings indicate that the use of pop-up book learning media significantly improves students’ learning outcomes in Civics learning. Therefore, pop-up book media can be considered an effective and engaging instructional tool for enhancing learning outcomes in elementary school classrooms.